Cost-effectiveness of WHO Problem Management Plus for adults with mood and anxiety disorders in a post-conflict area of Pakistan: randomised controlled trial. (November 2020) - Hamdani, Syed Usman; Huma, Zill-e-; Rahman, Atif; Wang, Duolao; Chen, Tao; van Ommeren, Mark; Chisholm, Dan; Farooq, Saeed
Abstract : Background: With the development of evidence-based interventions for treatment of priority mental health conditions in humanitarian settings, it is important to establish the cost-effectiveness of such interventions to enable their scale-up. Aims: To evaluate the cost-effectiveness of the Problem Management Plus (PM+) intervention compared with enhanced usual care (EUC) for common mental disorders in primary healthcare in Peshawar, Pakistan. Trial registration ACTRN12614001235695 (anzctr.org.au ). Method: We randomly allocated 346 participants to either PM+ ( n = 172) or EUC ( n = 174). Effectiveness was measured using the Hospital Anxiety and Depression Scale (HADS) at 3 months post-intervention. Cost-effectiveness analysis was performed as incremental costs (measured in Pakistani rupees, PKR) per unit change in anxiety, depression and functioning scores. Results: The total cost of delivering PM+ per participant was estimated at PKR 16 967 (US$163.14) using an international trainer and supervisor, and PKR 3645 (US$35.04) employing a local trainer. The mean cost per unit score improvement in anxiety and depression symptoms on the HADS was PKR 2957 (95% CI 2262–4029) (US$28) with an international trainer/supervisor and PKR 588 (95% CI 434–820) (US$6) with a local trainer/supervisor. The mean incremental cost-effectiveness ratio (ICER) to successfully treat a case of depression (PHQ-9 ≥ 10) using an international supervisor was PKR 53 770 (95% CI 39 394–77 399) (US$517), compared with PKR 10 705 (95% CI 7731–15 627) (US$102.93) using a local supervisor. Conclusions: The PM+ intervention was more effective but also more costly than EUC in reducing symptoms of anxiety, depression and improving functioning in adults impaired by psychological distress in a post-conflict setting of Pakistan.